Magnetic structure and excitations of the topological semimetal YbMnBi2 - Soh, J; Jacobsen, H; Ouladdiaf, B; Ivanov, A; Piovano, A; Tejsner, T; Feng, Z; Wang, H; Su, H; Guo, Y; Shi, Y; Boothroyd, A (American Physical Society, 2019)
We investigated the magnetic structure and dynamics of YbMnBi2, with elastic and inelastic neutron scattering, to shed light on the topological nature of the charge carriers in the antiferromagnetic phase. We confirm C-type antiferromagnetic ordering of the Mn spins below TN = 290 K and determine that the spins point along the c axis to within about 3◦. The observed magnon spectrum can be described very well by the same effective spin Hamiltonian that was used previously to model the magnon spectrum of CaMnBi2. Our results show conclusively that the creation of Weyl nodes in YbMnBi2 by the time-reversal symmetry-breaking mechanism can be excluded in the bulk.